Golden Fibonacci

lim n 2 F n + 8 F n = F α F β + F γ F δ \lim _{ n\rightarrow \infty }{ \frac { 2{ F }_{ n+8 } }{ { F }_{ n } } } ={ F }_{ \alpha }\sqrt { { F }_{ \beta } } +{ F }_{ \gamma }-F_{ \delta } Let F n F_n denote the n th n^\text{th} Fibonacci number . Find α + β + γ + δ \alpha +\beta +\gamma +\delta .


This problem is original.


The answer is 29.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Josh Banister
Jan 5, 2016

Let F n = a F_n = a and F n + 1 = b F_{n+1} = b . By repeating the formula F k = F k 1 + F k 2 F_k = F_{k-1} + F_{k-2} for all integers k 3 k \geq 3 , we get F n + 2 = a + b F_{n+2} = a+b , F n + 3 = a + 2 b F_{n+3} = a+2b , \dots , F n + 8 = 13 a + 21 b F_{n+8} = 13a + 21b .

From this, we can get lim n 2 F n + 8 F n = lim n 26 a + 42 b a = lim n 26 + 42 b a = 26 + 42 ( lim n F n + 1 F n ) \begin{aligned} \lim_{n\to\infty} \frac{2F_{n+8}}{F_n} &= \lim_{n\to\infty} \frac{26a + 42b}{a} \\ &= \lim_{n\to\infty} 26 + 42 \frac{b}{a} \\ &= 26 + 42 \bigg( \lim_{n\to\infty} \frac{F_{n+1}}{F_n} \bigg) \end{aligned}

It is well established that lim n F n + 1 F n = φ = 1 + 5 2 \lim_{n\to\infty} \frac{F_{n+1}}{F_n} = \varphi = \frac{1+\sqrt{5}}{2} and thus we substitute this in and we get lim n 2 F n + 8 F n = 26 + 42 ( 1 + 5 2 ) = 47 + 21 5 = 55 8 + 21 5 = F 10 F 6 + F 8 F 5 \begin{aligned} \lim_{n\to\infty} \frac{2F_{n+8}}{F_n} &= 26 + 42 (\frac{1+\sqrt{5}}{2}) \\ &= 47 + 21\sqrt{5} \\ &= 55 -8 + 21\sqrt{5} \\ &= F_{10} - F_6 + F_8\sqrt{F_5} \end{aligned}

This gives us a solution of 5 + 6 + 8 + 10 = 29 5 + 6 + 8 + 10 = \boxed{29}

I wanted to point out that previously, I thought that the question asked for the answer to be of the from F α + F β + F γ F δ F_{\alpha} + F_{\beta} + F_{\gamma}\sqrt{F_{\delta}} (without the minus sign). In this case, you can still get the right answer of 29 since F n + F n + 2 = F n + 3 F n 1 F_n + F_{n+2} = F_{n+3} - F_{n-1} for all integers n > 1 n > 1 . I got 47 + 21 5 = F 10 F 6 + F 8 F 5 = F 7 + F 9 + F 8 F 5 47 + 21\sqrt{5} = F_{10} - F_6 + F_8\sqrt{F_5} = F_7 + F_9 + F_8\sqrt{F_5} giving the final sum to be 5 + 7 + 8 + 9 = 29 5 + 7 + 8 + 9 = \boxed{29}

I think your solution is wrong since you have not expressed the solution in the form as the question asks. Please recheck your solution's last steps. But still, your answer is correct and you have done everything else right.

Anupam Nayak - 5 years, 5 months ago

Fibonacci sequence is linear recurrent sequence tha follows the Binet's formula: F n = φ n ( φ ) n 5 F_n = \dfrac{\varphi^n - (-\varphi)^{-n}}{\sqrt{5}} , where φ = 1 + 5 2 \varphi = \dfrac{1+\sqrt{5}}{2} , the golden ratio. Therefore, we have:

lim n 2 F n + 8 F n = lim n 2 ( φ n + 8 ( φ ) n 8 ) φ n ( φ ) n = lim n 2 ( φ n + 8 n ( φ ) n 8 n ) φ n n ( φ ) n n = lim n 2 ( φ 8 ( φ ) 2 n 8 ) 1 ( φ ) 2 n = 2 φ 8 \begin{aligned} \lim_{n \to \infty} \frac{2F_{n+8}}{F_n} & = \lim_{n \to \infty} \frac{2(\varphi^{n+8} - (-\varphi)^{-n-8})}{\varphi^n - (-\varphi)^{-n}} \\ & = \lim_{n \to \infty} \frac{2(\varphi^{n+8-n} - (-\varphi)^{-n-8-n})}{\varphi^{n-n} - (-\varphi)^{-n-n}} \\ & = \lim_{n \to \infty} \frac{2(\varphi^{8} - (-\varphi)^{-2n-8})}{1 - (-\varphi)^{-2n}} \\ & = 2\varphi^8 \end{aligned}

Since φ \varphi is a root of x 2 x 1 = 0 x^2 - x - 1 = 0 or x 2 = x + 1 x^2=x+1 , therefore,

φ 2 = φ + 1 φ 4 = ( φ + 1 ) 2 = φ 2 + 2 φ + 1 = 3 φ + 2 φ 8 = ( 3 φ + 2 ) 2 = 9 φ 2 + 12 φ + 4 = 21 φ + 13 \begin{aligned} \varphi^2 & = \varphi + 1 \\ \varphi^4 & = (\varphi + 1)^2 = \varphi^2 + 2\varphi + 1 = 3\varphi + 2 \\ \varphi^8 & = (3\varphi + 2)^2 = 9\varphi^2 + 12\varphi + 4 = 21\varphi + 13 \end{aligned}

lim n 2 F n + 8 F n = 2 φ 8 = 2 ( 21 φ + 13 ) = 2 ( 21 ( 1 + 5 2 + 13 ) = 21 5 + 47 = 21 5 + 55 8 = F 8 F 5 + F 10 F 6 \begin{aligned} \Rightarrow \lim_{n \to \infty} \frac{2F_{n+8}}{F_n} & = 2\varphi^8 \\ & = 2 \left(21\varphi + 13 \right) \\ & = 2 \left(\frac{21(1+\sqrt{5}}{2} + 13 \right) \\ & = 21\sqrt{5} + 47 \\ & = 21\sqrt{5} + 55 - 8 \\ & = F_8 \sqrt{F_5} + F_{10} - F_6 \end{aligned}

α + β + γ + δ = 8 + 5 + 10 + 6 = 29 \Rightarrow \alpha + \beta + \gamma + \delta = 8 + 5 + 10 + 6 = \boxed{29}

Nice solution. (You have left a bracket unclosed in the last part of your solution's third line.)

Anupam Nayak - 5 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...